Manila Bay Wetland Center proposed ecotourism center for Las Piñas-Parañaque critical habitat and ecotourism area - Marchadesch, Angelo Neil R.
The Manila Bay Ecotourism Center came upon as an answer to the neglect of the government to Manila Bay’s ecological properties. The main problem encountered is the fact that the government doesn’t place much importance in lands that don’t bring in revenue, which leads to them selling these lands to developers at the cost of ecological destruction. This can also be attributed to the lack of awareness on the advantages of wetlands, hence the creation of the Manila Bay Ecotourism Center. The primary purpose of the project is to educate the users on the importance of wetlands and their functions and highlight the role of nature in an urban environment. The goal of the project is to become the premiere example of an ecotourism destination for the country’s protected areas. Different sustainability practices were tackled such as the in-site cultivation and use of bamboo as renewable material and the cyclical process of using water in the site, to show that we need not destroy nature, rather we should harmonize with nature. By bridging the natural and the built environments together, we create a more wholistic approach to ecotourism that can be used as a template in different parts of the country.